A country enters the process of setting prices as a limitation to freedom of competition in Algerian legislation - Meskine, Hanane; Benahmed, Elhadj (Journal of Human Sciences, 2021)
The constitutional legislator stipulated freedom of trade and industry as a constitutional principle, which resulted in freedom of competition, and the latter is based only on freedom of prices, which is one of the basic principles upon which competition is based as a general principle, but this principle is not taken to launch it, so the state may interfere To set prices in line with certain conditions and by using specific mechanisms under the law to fight speculation and protect the consumer. The aim of this research paper is to protect the purchasing power of the consumer and ensure market stability. Perhaps the question that arises in this regard is: To what extent is the state involved in the process of setting prices? To answer this question, we adopted the descriptive and analytical method, divided the subject of the study into three axes, each of which includes specific elements.